Absolutyzacja woli ludu jako źródło degeneracji ustroju demokratycznego - Kimla, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The aim of the article is to outline the distinction between the nomocratic and the voluntarist version of democracy. Based of the findings of classical political philosophy, I strive to show that democracy can also turn into tyranny, the basic feature of which is the instability of the law. The main issue I am considering is the question of how to limit the will of the people without placing any other will above people’s will. In the past, this was achieved by depoliticizing the people. Today, however, this path seems closed due to, among other things, the constant pressure on the people to take a stand. The people are convinced by party leaders that they are a many-headed monarch and that their will is above the law. This creates the conditions for the emergence and functioning of a voluntarist democracy, which is a tyranny of the majority. Thus, the prospects for the development of a nomocratic democracy, in which the people are seen as guardians of law, are not bright.
Keywords: demokracja; nomokracja; wola ludu; tyrania; rządy prawa